MODEL PROBLEM BASED LEARNING DALAM MENULIS TEKS EKSPLANASI - Fauziatun Azhima (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2022)
Explanatory text is a new material that is taught in schools so that most students have not fully mastered the material related to explanatory text. The teacher's role in learning is as a manager, organizer and facilitator during learning. In carrying out their role, teachers have an obligation to produce effective and meaningful learning. The skills that must be possessed by students, both soft skills and hard skills to match the targets set by the government can be achieved by applying the problem based learning model. The skills that must be possessed by students, both soft skills and hard skills to match the targets set by the government can be achieved by applying a problem based learning model that allows students to train students to integrate knowledge and skills simultaneously and apply them in relevant contexts.